2009
DOI: 10.1007/s12640-009-9011-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Symptomatic and Neuroprotective Efficacy of Mucuna Pruriens Seed Extract in Rodent Model of Parkinson’s Disease

Abstract: Mucuna pruriens (MP) has long been used in Indian traditional medicine as support in the treatment of Parkinson's disease. However, no systematic preclinical studies that aimed at evaluating the efficacy of this substance are available to date. This study undertook an extensive evaluation of the antiparkinsonian effects of an extract of MP seeds known to contain, among other components, 12.5% L: -dihydroxyphenylalanine (L: -DOPA), as compared to equivalent doses of L: -DOPA. Moreover, the neuroprotective effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 27 publications
1
40
1
2
Order By: Relevance
“…In many countries, this plant is also used in the treatment of cholesterol, diabetes, hypertension, paralysis, rheumatism, cancer, tumors, tuberculosis, asthma, cholera, diarrhea, dysentery, irritation, burns, cough, muscle pain, and many others [5][6][7]. Various studies reported the bioactivity of Mucuna pruriens, such as increasing the sexual activity of normal male rats, hepatoprotective activity with increasing the in vivo antioxidants [8], antidiabetic activity [9][10][11][12], and as a potential antiparkinson from the seeds [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In many countries, this plant is also used in the treatment of cholesterol, diabetes, hypertension, paralysis, rheumatism, cancer, tumors, tuberculosis, asthma, cholera, diarrhea, dysentery, irritation, burns, cough, muscle pain, and many others [5][6][7]. Various studies reported the bioactivity of Mucuna pruriens, such as increasing the sexual activity of normal male rats, hepatoprotective activity with increasing the in vivo antioxidants [8], antidiabetic activity [9][10][11][12], and as a potential antiparkinson from the seeds [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It was especially reported that MPTP induces the degeneration of spinal cord in a mouse model of MPTP intoxication (Samantaray et al, 2008). Pharmaceutical studies have been conducted using these animal models of PD-like neuropathological features as well as using actual PD patients (Dutta et al, 2008;Etminan et al, 2003;Hamaue 2000;Kasture et al, 2009;Liang et al, 2007;Neef and van Laar, 1999;Yano et al, 2009). However, these studies have not yet led to the development of satisfactory anti-parkinsonism drugs with longterm therapeutic effects for PD patients; for example, long-term treatment with Levodopa (a drug used to treat PD) is known to cause serious side effects such as dyskinesia (Calon et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Mucuna pruriens has been shown to contain natural levodopa (LD, [5–11]), which has been presumed to be the mechanism of its action in PD. Under this presumption, many experimental studies have concomitantly administered Mucuna pruriens with a dopa-decarboxylase inhibitor (DDCI) like benserazide (BZ, [12]) or carbidopa (CD, [13]); or used subjects that concurrently took a DDCI as part of their treatment regimen without adequate washout [14]. However, no DDCI is utilized in Ayurveda with Mucuna pruriens treatment.…”
Section: Introductionmentioning
confidence: 99%